The Relationship Between Attractiveness and Recognition Memory for Faces - Kinsky, Alex (The University of Edinburgh, 2011)
Previous research into the relationship between attractiveness and recognition memory for faces has produced no conclusive findings, therefore this study used an ‘old’/’new’ recall task in attempt to clarify the relationship. The debate appears to be linked to the relationship between attractiveness and distinctiveness, and the literature surrounding this matter is discussed. Participants were asked to rate faces for attractiveness and then at a later stage subjected to the recognition task. Both attractive and unattractive faces were found to better recognised than faces rated at neither end of the attractiveness spectrum. Very unattractive faces were recognised faster than attractive faces. There were also an effect of gender, with female participants performing significantly worse than males when it came to recognising very unattractive male faces. The implications of all of these results, as well as the possible reasons why other studies into the topic area have not reported the same findings, are discussed.
Keywords: Psychology